Formation of Participatory Village Regulations in the Implementation of Democratic Village Government Based on Pancasila Democracy - Neta, Yulia; Akib, Muhammad; Ridlwan, Zulkarnain; Tisnanta, HS; Evendia, Malicia; Awanisa, Agsel (Journal of Ecohumanism, 2025)
The purpose of this article is to analyze the institutionalization and implementation of the formation of participatory village regulations, the importance of the formation of participatory village regulations for the implementation of village democracy, the model of the formation of participatory village regulations based on Pancasila democratic values. PProblems in the practice of forming village regulations show that so far the community in general has only given its trust to the village head and the Village Consultative Body (BPD) in forming village regulations.This study uses a normative legal research method using a statutory regulatory approach and a conceptual approach. The results of this study indicate that the participatory model of village regulation formation based on Pancasila Democracy is an approach that aims to strengthen village governance through an inclusive, transparent, and accountable legislative process. Village deliberation is the main mechanism in this model, providing a deliberative forum where various views and interests can be conveyed and discussed openly. Thus, the village government needs to adopt an effective communication mechanism to convey information related to the legislative process to the community.